Performance of egg production, fertility and hatchability of turkey in different production systems - Adhikari, Dipak; Paudel, Sagar; Sapkota, Saroj; Shrestha, Snehi; Poudel, Nabaraj; Bhattari, Nirajan (Journal of Nepal Agricultural Research Council, 2024)
Turkey (Meleagris gallopavo) is a popular poultry species which is able to adopt wide range of climatic condition and called by charismas chicken. A study was conducted in Swine and Avian Research Program, Khumaltar, Lalitpur to evaluate the egg production, fertility and hatchability of turkey in intensive and semi-intensive production system. This study was carried out from April 2019 to July 2020 that included 80 female and 16 male breeding turkeys. Among them 40 female and 8 male were kept under each system. In semi-intensive system turkeys started to lay eggs within 41 weeks and 10 % eggs production was received in 45 weeks whereas in intensive system one week more time was taken in both aspects. The hatchability in semi-intensive system was found 79.33±6.13 % whereas 43.09±9.70 % in case of intensive system. In case of fertility, in semi-intensive system it was found 84.77±2.98% and 53.68±5.40 % in intensive system. The eggs production was also much more different in both systems. In semi-intensive system, it was found 36.89±15.78 % and only 31.90±12.45% in intensive system. In the main breeding season from February to July per bird produced only 67 eggs in semi-intensive system and 58 in intensive system. The factors such as production system and months were significantly influenced (P<0.001) in all productive traits. In both system, egg production and hatchability was more in April, May and June so this three month called peak egg production in Turkey. The hatchability of Turkey reared under semi-intensive system was much better which might be due to their grazing habit which helped to decrease aggressiveness of turkeys and did not disturb during matting time. Similarly, the wound in back of female turkey was less in semi-intensive system.Therefore semi-intensive production system is better in turkey for egg production, fertility and hatchability.